Bonus Pools, Limited Liability, and Tournaments - Jörg Budde (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2007)
Tournaments have been objected as resulting from ad hoc restrictions to the contracting problem which are not easily justified. Taking into account that a performance measure might not be verifiable to a third party, however, a restriction to payments which sum up to a constant may be reasonable. The paper analyzes such fixed payment schemes with regard to their optimality and the relation to the special case of tournaments. It emerges that for a group of identical risk-neutral agents, the optimal fixed payment scheme is a tournament.
urn:nbn:de:bvb:19-epub-13347-6
Keywords: D82; M52; M54; 330; bonus pools; relative performance evaluation; subjective performance evaluation; tournaments; verifiability